STRUKTUR POPULASI (Pinus merkusii Jungh et de Vriese) DI KAWASAN DANAU SARI EMBUN KABUPATEN TANAH LAUT: POPULATION STRUCTURE (Pinus merkusii Jungh et de Vriese) IN THE LAKE SARI EMBUN AREA, TANAH LAUT DISTRICT - Raihani, Salsabila; Dharmono, Dharmono; Amintarti, Sri (Biospecies, 2023)
Population structure is defined as an arrangement of age classes in a population. It is very important to study population structure to determine the status and existence of a population so that efforts can be made to control the population in that habitat. Pine is one of the plants found in the Danau Sari Embun area which has the potential to be used as a learning resource based on local content. The results of data analysis show that the population structure of Pine plants in the Danau Sari Embun area was found to be 0 Ind/2.5 Ha in the pre-reproductive phase, 14 Ind/2.5 Ha in the reproductive phase, 0 Ind/2 Ha in the post-reproductive phase. .5 Ha, so that the shape of the pyramid is in the form of a vase or jug with a disturbed base. Keywods: Population Structure, Pinus merkusii, Danau Sari Embun Â  Abstrak Struktur populasi didefinisikan sebagai suatu susunan kelas umur dalam suatu populasi. Kajian tentang struktur populasi sangat penting dilakukan untuk mengetahui status dan keberadaan suatu populasi sehingga dapat dilakukan upaya untuk penanggulangan populasi dihabitat tersebut. Pinus adalah salah satu tumbuhan yang terdapat di kawasan Danau Sari embun yang berpotensi dijadikan sebagai sumber belajar berbasis muatan lokal. Hasil analisis data menunjukkan bahwa struktur populasi tumbuhan Pinus di kawasan Danau Sari embun di dapatkan jumlah pada fase pra-reproduktif berjumlah 0 Ind/2,5 Ha, fase reproduktif berjumlah 14 Ind/2,5Ha, fase post-reproduktif berjumlah 0 Ind/2,5Ha, sehingga bentuk piramidanya berbentuk pasu atau kendi dengan dasar terganggu. Kata Kunci: Struktur Populasi, Pinus merkusii, Danau Sari Embun